Human leukocyte immunoglobulin-like receptors in health and disease - Redondo-García, Silvia; Barritt, Christopher; Papagregoriou, Charys; Yeboah, Muchaala; Frendeus, Björn; Cragg, Mark S.; Roghanian, Ali (Frontiers in Immunology, 2023)
Human leukocyte immunoglobulin (Ig)-like receptors (LILR) are a family of 11 innate immunomodulatory receptors, primarily expressed on lymphoid and myeloid cells. LILRs are either activating (LILRA) or inhibitory (LILRB) depending on their associated signalling domains. With the exception of the soluble LILRA3, LILRAs mediate immune activation, while LILRB1-5 primarily inhibit immune responses and mediate tolerance. Abnormal expression and function of LILRs are associated with a range of pathologies, including immune insufficiency (infection and malignancy) and overt immune responses (autoimmunity and alloresponses), suggesting LILRs may be excellent candidates for targeted immunotherapies. This review will discuss the biology and clinical relevance of this extensive family of immune receptors and summarise the recent developments in targeting LILRs in disease settings, such as cancer, with an update on the clinical trials targeting these receptors.